(untitled) (Journal of Governance and Development (JGD), 2025)
Information and its authenticity are necessary for a viable political system. This is because once ‘political’ news about certain issues or situations in the polity is not trusted or deemed as false, the importance of such information may be treated by the public with nonchalance. This study examines the implications of misinformation during the just-concluded 2023 general elections in Nigeria and the extent to which it has created distrust in the minds of the masses regarding the information the government disseminated to the public. It adopts the conspiracy perspective on fake news as a theoretical guide to show the prevailing situation in the nation. Data for this paper will be retrieved from secondary sources, specifically those with relevant information on the 2023 elections. These will be explained using the discourse analysis method of data analysis. Findings from the study reveal that misinformation regarding candidates and the election umpire was peddled during the 2023 general elections. This led to low voter turnout in some parts of the country. The study suggests that the government take stringent sanctions against those involved in spreading unverified news to control the damage of such information on the polity.